2018
DOI: 10.3389/fmicb.2018.00048
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Heterogeneity and Co-occurrence of Mucosal and Luminal Microbiome across Swine Intestinal Tract

Abstract: Pigs are one of the most important economic livestock. Gut microbiota is not only critical to the health but also the production efficiency of pigs. Manipulating gut microbiota relies on the full view of gut microbiome and the understanding of drive forces shaping microbial communities. 16s rDNA sequencing was used to profile microbiota along the longitudinal and radical axes to obtain the topographical map of microbiome in different intestinal compartments in young pigs. Alpha and beta-diversities revealed di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
140
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(164 citation statements)
references
References 70 publications
22
140
2
Order By: Relevance
“…In term of microbial composition, ileum samples were drastically different from caecum and colonic samples which were highly similar (81,83,84,86,87). Moreover, in the present study we also confirmed that mucosa samples have higher richness than lumen samples regardless of the location in the gut tract (82,85,88). The three most abundant phyla determined in this study: Firmicutes, Bacteroidetes, and Proteobacteria also matched what is always reported for pigs at that age (73,79,82,86,87,89).…”
Section: Streptococcus D14supporting
confidence: 88%
See 1 more Smart Citation
“…In term of microbial composition, ileum samples were drastically different from caecum and colonic samples which were highly similar (81,83,84,86,87). Moreover, in the present study we also confirmed that mucosa samples have higher richness than lumen samples regardless of the location in the gut tract (82,85,88). The three most abundant phyla determined in this study: Firmicutes, Bacteroidetes, and Proteobacteria also matched what is always reported for pigs at that age (73,79,82,86,87,89).…”
Section: Streptococcus D14supporting
confidence: 88%
“…tract (79)(80)(81)(82)(83)(84)(85). In term of microbial composition, ileum samples were drastically different from caecum and colonic samples which were highly similar (81,83,84,86,87).…”
Section: Streptococcus D14mentioning
confidence: 96%
“…At the genus level, the relative abundance of Alloprevotella, Prevotella-2, and Prevotellaceae_NK3B31_group bacteria in HPC sows was higher while the relative abundance of Ruminococcaceae_UCG-005, Ruminococcaceae_UCG-002 and Ruminococcaceae_NK4A214_group was significantly lower than LPC sows at LP stage. Prevotellaceae is correlated with amino acids, energy and vitamins metabolism (Zhang et al, 2018). Ruminococcaceae is negatively associated with Lipopolysaccharide (LPS) biosynthesis and lower Ruminococcaceae might contribute to inflammatory environment.…”
Section: Discussionmentioning
confidence: 99%
“…Further, BUN level showed a negative correlation with Ruminococcaceae. Ruminococcaceae is related to amino acids metabolism (Zhang et al, 2018). Thus, the BUN differences might be caused by Ruminococcaceae.…”
Section: Discussionmentioning
confidence: 99%
“…This post-weaning microbiome may therefore, have a greater capacity to breakdown the diet, driving the improved performance in the laminarin supplemented pigs. Zhang et al [31] identified a co-exclusion relationship between Enterobacteriaceae and Prevotellaceae. These authors highlighted the greater capacity of members of the Prevotellaceae family to digest complex carbohydrates into VFAs which can directly reduce the colonization of Enterobacteriaceae by lowering intestinal pH and reducing inflammation.…”
Section: Discussionmentioning
confidence: 99%